Monte Carlo simulation of mixed nonionic Brij surfactants in water - Yahya, Ruzanna; Karjiban, Roghayeh Abedi; Basri, Mahiran; Abdul Rahman, Mohd Basyaruddin; Girardi, Mauricio (Springer, 2014)
Nonionic surfactants such as the Brij® series are important in the preparation of transdermal drug nanodelivery products using nanoemulsions because of their low toxicity and low irritancy. Here, Monte Carlo (MC) simulation was used to examine the physical behavior of the model deterministic system by using sampling procedures. Metropolis MC simulations were run on three mixtures of two different nonionic surfactants, Brij92 and Brij96, with different compositions in aqueous solution. The system was simulated in the canonical ensemble with constant temperature, volume and number of molecules. Hence, the acceptance ratio for single atom moves of the mixed surfactants increased as the concentration of surfactants increased from 0.494 to 0.591. The lowest total energy for the mixed surfactant systems was −99,039 kcal mol−1 due to the interaction between all molecules in the system simulated. The physicochemical properties of models such as the radius of gyration and radial distribution function, were also determined. These observations indicate that the behavior and physicochemical of mixed surfactant and PKOEs nanoemulsion systems were described adequately during the simulation.